PENGOLAHAN SAMPAH RUMAH TANGGA ORGANIK MENJADI PUPUK ORGANIK DI DESA SUMBERSARI - Bagaskoro, Angga Dwi; Juliandara, luthpiyah; Iskandar, Tatang (An-Nizam, 2023)
This community service reflects the increasing waste problem in Indonesia, especially in Bekasi Regency, which is caused by population growth and the lack of adequate waste management infrastructure. Organic waste is the main component of waste produced in residential areas and can contribute to environmental and health problems. A waste management approach based on community participation is a solution to reduce the negative impacts of this waste. Recycling is also an important alternative in overcoming the waste problem in urban areas. This research tries to overcome the knowledge gap in the community, especially in Hamlet 1 Sumbersari through education and outreach about managing household organic waste into compost. The methods used include community education, science and technology diffusion, and training. The results of implementing this program show that the community can understand and carry out the processing of organic waste into compost well. Implementation of this program provides significant benefits in increasing public awareness about waste management and recycling. Apart from that, the implementation of this program also has a positive impact on the environment and economy. By increasing understanding about organic waste management, the community can actively participate in reducing waste production and improving the quality of agricultural land through the use of organic fertilizer. Thus, this approach can be a positive step in overcoming the waste problem and improving the quality of life of the community in Sumbersar Village and its surroundings.